Analisis Nilai Pendidikan Islam dan Nilai Pendidikan Karakter Pemimpin Melalui Tembang Tradisional Lagu Lir-ilir Karya Sunan Kalijaga - Juliastuti, Juliastuti; Hidayat, Sholeh; Jamaludin, Ujang; Leksono, Suroso Mukti (SAP (Susunan Artikel Pendidikan), 2024)
This study aimed to analyze the value of Islamic education and the value of character education of leaders through the traditional song Lir-ilir by Sunan Kalijaga. This study used descriptive qualitative methods and library research. Data was collected from language objects or primary sources using Lir-ilir songs studied. Researchers used documentation methods, namely seeking information about existing variables in words, sentences, and implicit or explicit messages from written and non-literary documents from various literary sources. Secondary data sources include books, scientific articles, magazines, and journals. The technique used in this study is semiotic analysis; the words of the Lir-ilir song are placed in a position as a sign system which the meaning needs to be analyzed. The results of this study indicate that: 1) the implied meaning of Lir-ilir song on Islamic educational values is as follows: shari'ah values, creed values, moral values to Allah SWT, moral values to others, moral values to the environment. 2) the implied meaning of Lir-ilir song on the value of character education of leaders are discipline values, religious values, creativity, environmental care, communication, responsibility, honesty, hard work, the spirit of control and support, and democracy.